Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6cp06082j
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced transformations of methanol molecules in low-temperature solids: a matrix isolation study

Abstract: The effect of X-ray irradiation on methanol molecules (CHOH, CDOH, and CHOH) isolated in solid noble gas matrices (Ne, Ar, Kr, and Xe) was studied by FTIR spectroscopy at 6 K. CHOH˙, HCO, HCO˙ and CO were found to be the main degradation products. Somewhat unexpectedly, the production of CO is quite prominent, even at low doses, and it strongly predominates in low-polarizable matrices (especially, in neon). This result is explained by inefficient quenching of excess energy in the HCO molecules initially genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 82 publications
(135 reference statements)
4
43
0
Order By: Relevance
“…A very small signal was detected at 606.6 cm −1 which according to Saenko & Feldman (2016) can be tentatively assigned to CH 3 radical. However, previous studies on this radical have attributed the out of plane mode of this radical to a band around 611-617 cm −1 , presenting notable dependence with the temperature (Milligan & Jacox 1967;Snelson 1970;Jacox 1977).…”
Section: Radical Formationmentioning
confidence: 90%
See 2 more Smart Citations
“…A very small signal was detected at 606.6 cm −1 which according to Saenko & Feldman (2016) can be tentatively assigned to CH 3 radical. However, previous studies on this radical have attributed the out of plane mode of this radical to a band around 611-617 cm −1 , presenting notable dependence with the temperature (Milligan & Jacox 1967;Snelson 1970;Jacox 1977).…”
Section: Radical Formationmentioning
confidence: 90%
“…Radicals of astrophysical interest were studied by this technique; Adrian et al (1962) presented the EPR spectrum of H CO radical and its deuterated form D CO in solid carbon monoxide from 4.2 K to 30 K. Zhitnikov & Dmitriev (2002) identified radicals in astro-relevant environments formed from hydrogenation of CO or CH 4 ices. There are also some known applications of EPR spectroscopy to the photochemical study of complex organic molecules in solid phase or trapped in solid glasses or cryogenic matrices and submitted to (Mao & Kevan 1974), X-rays (Toriyama & Iwasaki 1979;Yamada et al 1999;Saenko & Feldman 2016) or VUV photolysis (Watanabe et al 2007;Tsegaw et al 2016). However, its application is not widespread in the astrochemical community, and we believe that its potential in this field has not been fully explored neither.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another band at 1385.3 cm -1 ( figure 4) behaves similarly as the bands at 609.2 and could also be due to the radical species CH 3 .We have assigned, based on water concentration effects and sample heating, the peak at 1191.8 cm -1 to CH 2 OH radicals (figure 3). Previous experimental studies involving radiation induced processing of H 2 CO and CH 3 OH ices have shown the formation of CH 2 OH through its most intense 24,25 26,27 to be located at 1173, 1125 and 1032 cm -1 . We have observed under our experimental conditions tow IR signals located at 1174.9 and 1124.1 cm -1 which may be assigned to CH 3 OCH 3 and CH 3 OCH 2 OH, respectively.…”
Section: → Ch and Oh Stretching Mode Region @ The 3500-2800mentioning
confidence: 95%
“…While the former process is probably hampered by the high barriers arising from the positive charges of the colliding partners, the PAHs route seems more plausible, especially in view of the predicted exothermic character of model reactions between NeH + and C 10 H 8 -Ng or C 32 H 14 -Ng (Ng = Ne, Ar) (Fortenberry, 2017). Other suggestions for conceivable formation routes come from studies performed in cold matrices (Feldman et al, 2016;Saenko and Feldman, 2016), showing that ionized molecules such as H 2 O and CH 3 OH (quite abundant in the outer space) might protonate Ng atoms so to eventually form the Ng-H-Ng + .…”
Section: Ng-h-ngmentioning
confidence: 99%